PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH, MOTIVASI KERJA, DISIPLIN KERJA TERHADAP KINERJA GURU DI SMPN 04 PUTUSSIBAU - Saputra, Ardianus Imen; Wicaksono, Luhur (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This study aims to examine and analyze the effect of leadership style, work motivation, work discipline on the performance of teachers at SMPN 04 Putussibau. This study uses a quantitative descriptive approach. The technique collected in the form of primary data through a questionnaire distributed to respondents called a questionnaire. The data collection technique used purposive sampling technique, namely the sampling technique with certain considerations, namely using certain criteria such as educators who have worked for more than 1 year, this research was conducted by distributing questionnaires to 30 teachers at SMPN 04 Putussibau. From the results of the study that the leadership style variable has no significant effect on teacher performance, the results of the multiple regression equation obtained a value of 0.055 with a t-count value of 0.206 smaller than t-table 2.055 and a Sig value of 0.840 greater than 0.05, then Ha is rejected. The work motivation variable has a significant effect on teacher performance, namely the value of the multiple regression equation produces a value of 0.596, with a t-count value of 2.217 smaller than t-table 2.0555 and a Sig value of 0.037 smaller than 0.05 then Ha is accepted. The work discipline variable has a significant effect on teacher performance, namely the value of the multiple regression equation obtained by a value of 0.790, with a value of 3.151 greater than t table 2.055 and a Sig value of 0.006 less than 0.05, then Ha is accepted. Leadership style, work motivation and work discipline simultaneously (simultaneously) have a significant effect on teacher performance at SMPN 04 Putussibau.